Perkembangan Dan Potensi Perekonomian Usaha Tanaman Hias Di Kelurahan Lubuk Minturun Koto Tangah Kota Padang (1991-2020) - Qothrunada Farhana Nabila; Azmi Fitrisia (Jurnal Kronologi, 2023)
This article discusses the development and economic potential of the ornamental plant business in Lubuk Minturun Koto Tangah Village, Padang City (1991-2020). The ornamental plant agribusiness business is currently growing rapidly. The city of Padang is the center of ornamental plants in West Sumatra. The first center for ornamental plants is located in Lubuk Min Koto Tangah, Padang City. This article is a historical approach research that prioritizes documents or archives and interviews as the main sources. To write the sources needed through a field approach through archives of nagari profiles in Lubuk Minturun Village, and documents for ornamental plant business people. This article shows that ornamental plant production increased in early 2020 due to the Covid-19 pandemic. Because in 2020 people's desire to plant flowers and grow crops at home is getting higher so that sales increase. The production of ornamental plants also has an impact on the social and economic life of ornamental plant farmers. This can be seen in terms of people's increased income, education that is starting to pay attention, ownership of property such as many who have renovated houses and bought vehicles.